2006
DOI: 10.1086/504688
|View full text |Cite
|
Sign up to set email alerts
|

Malaria, Anemia, and Malnutrition in African Children—Defining Intervention Priorities

Abstract: Malnutrition is a fundamental factor contributing to malaria-associated morbidity and anemia, even if the latter exhibits multifactorial patterns. Our data demonstrate that malaria-control programs alone may not have the desired impact on childhood morbidity on a large scale without concomitant nutrition programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
159
8
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 38 publications
14
159
8
2
Order By: Relevance
“…A possible explanation is because skin infections do not alter dietary intake as much as respiratory infections or gastroenteritis. Other studies have demonstrated a relationship between malaria and nutrtion, 21,22 but the low number of children in this study that is diagnosed with malaria, with a total of 5 makes it hard to show a significant effect. From the result of this study, regarding nutritional status in children, the focus should not be solely on improving the anthropometry status of children, but to also consider the overall health condition, because upper respiratory tract infections and gastroenteritis is caused by many different factors.…”
Section: Relationship Between Weight Gain and Infectioncontrasting
confidence: 65%
“…A possible explanation is because skin infections do not alter dietary intake as much as respiratory infections or gastroenteritis. Other studies have demonstrated a relationship between malaria and nutrtion, 21,22 but the low number of children in this study that is diagnosed with malaria, with a total of 5 makes it hard to show a significant effect. From the result of this study, regarding nutritional status in children, the focus should not be solely on improving the anthropometry status of children, but to also consider the overall health condition, because upper respiratory tract infections and gastroenteritis is caused by many different factors.…”
Section: Relationship Between Weight Gain and Infectioncontrasting
confidence: 65%
“…47 Thus, the indirect protection against stunting in children by HbAS might provide a further indirect survival advantage. The observation of a lower risk of malaria but more severe manifestations in carriers of HbSS corresponds to recent data from Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, nutrition strongly shapes malaria outcomes: Low levels of key micronutrients account for a substantial proportion of malaria morbidity and mortality (26,94). Improved childhood nutrition is likely to substantially reduce the burden of malaria in the developing world (2,95,96).…”
Section: Health and Disease Systemmentioning
confidence: 99%